Analisis Manajemen Risiko pada UMKM “Tahu Walek Ponkq” Jember - Dian Septi; Amelia Putri Maharani; Abu Bakar Abdul Rachman Bazed; Arya Abim Abdillah; Nurul Qomariah; Nursaid Nursaid (BUDGETING : Journal of Business, Management and Accounting, 2023)
Every business that is undertaken must have competition to increase business. Small, medium enterprises or commonly called SMEs are businesses that are easy to run for everyone who wants to do business. Competition will always exist in every area of life, including MSME businesses. Every business that is run must have competition and challenges that must be faced. To face competition and challenges in the business world, every MSME must innovate products and services, as well as develop human and technological resources. Every business that is carried out must contain risks. Therefore, as MSMEs, it is also necessary to know what risk management is. Risk management is needed to anticipate or reduce the possibility of risk occurring in a business. This paper aims to describe the risks faced by UMKM Tahu Walek "PONKQ" Jember. The analytical method uses descriptive analysis obtained from interviews with UMKM Tahu Walek "PONKQ" Jember. The results of the analysis show that UMKM Tahu Walek PongQ Jember has risks, namely raw material risk, financial risk, marketing risk. the. Based on the SWOT analysis owned by PONKQ Jember Tahu Walek UMKM, the strength is that this tahu walek is a new type of culinary, so there are lots of devotees. The weakness of this walek tofu business is that the raw material spoils quickly if there are leftovers. The opportunity from this business is that it can be developed to a wider area. Meanwhile, the threat from the tofu walek culinary business is from the same business and the culinary originating from tofu as well. Keywords: Culinary business, Risk management, UMKM tofu walek.